The role of binding domains for dsRNA and Z-DNA in the in vivo editing of minimal substrates by ADAR1 - Herbert, Alan (The National Academy of Sciences, 2001)
RNA editing changes the read-out of genetic information, increasing the number of different protein products that can be made from a single gene. One form involves the deamination of adenosine to form inosine, which is subsequently translated as guanosine. The reaction requires a double-stranded RNA (dsRNA) substrate and is catalyzed by the adenosine deaminase that act on dsRNA (ADAR) family of enzymes. These enzymes possess dsRNA-binding domains (DRBM) and a catalytic domain. ADAR1 so far has been found only in vertebrates and is characterized by two Z-DNA-binding motifs, the biological function of which remains unknown. Here the role of the various functional domains of ADAR1 in determining the editing efficiency and specificity of ADAR1 is examined in cell-based assays. A variety of dsRNA substrates was tested. It was found that a 15-bp dsRNA stem with a single base mismatch was sufficient for editing. The particular adenosine modified could be varied by changing the position of the mismatch. Editing efficiency could be increased by placing multiple pyrimidines 5′ to the edited adenosine. With longer substrates, editing efficiency also increased and was partly due to the use of DRBMs. Additional editing sites were also observed that clustered on the complementary strand 11–15 bp from the first. An unexpected finding was that the DRBMs are not necessary for the editing of the shorter 15-bp substrates. However, mutation of the Z-DNA-binding domains of ADAR1 decreased the efficiency with which such a substrate was edited.